High pressure control of protein structure and functionality. Issue 1 (2014) - Amar Aouzelleg
<x xml:space="preserve"> Abstract </x> Purpose – This article aims to consider the use of high pressure processing in order to gain functional advantages through proteins structure control. High pressure processing has been used to produce high‐quality food with extended shelf life and could also be used to modify foods functionality. Design/methodology/approach – The effect of high pressure on protein structure and functionality is looked at and comparisons are made with heat effect in places. β‐lactoglobulin and whey proteins are mainly taken as examples. Findings – A controlled partial protein unfolding through mild high pressure processing could lead to a range of intermediate molecular structures. These are distinct from the native and completely unfolded structure and have been referred to as molten globules. The partly unfolded molecular states, hence, are postulated to have increased functionality and could be interesting for the food industry. Originality/value – The opportunity and challenges represented by these theoretical elements are discussed. In particular, the effect of protein concentration and aggregation is emphasised.